Clockwork angel eaudiobook - Clare, Cassandra (The Infernal Devices, 2010)
Magic is dangerous—but love is more dangerous still. Discover the "compulsively readable" ( Booklist ) first book in the #1 New York Times bestselling Infernal Devices trilogy, prequel to the internationally bestselling Mortal Instruments series! Clockwork Angel is a Shadowhunters novel. When Tessa Gray crosses the ocean to find her brother, her destination is England, the time is the reign of Queen Victoria, and something terrifying is waiting for her in London's Downworld, where vampires, warlocks, and other supernatural folk stalk the gaslit streets. Only the Shadowhunters, warriors dedicated to ridding the world of demons, keep order amidst the chaos. Kidnapped by a secret organization called The Pandemonium Club, Tessa learns that she herself is a Downworlder with a rare ability: the power to transform into another person. What's more, the Magister, the shadowy figure who runs the Club, will stop at nothing to claim Tessa's power for his own. Friendless and hunted, Tessa takes refuge with the Shadowhunters of the London Institute, who swear to find her brother if she will use her power to help them. She soon finds herself fascinated by—and torn between—two best friends: James, whose fragile beauty hides a deadly secret, and Will, whose caustic wit and volatile moods keep everyone in his life at arm's length...everyone, that is, but Tessa. As their search draws them deep into the heart of an arcane plot that threatens to destroy the Shadowhunters, Tessa realizes that she may need to choose between saving her brother and helping her new friends save the world...and that love may be the most dangerous magic of all.